Recent evidence for the effects of nonnutritive sweeteners on glycaemic control. Issue 4 (July 2019) - Ahmad, Samar Y.; Azad, Meghan B.; Friel, James; MacKay, Dylan
Abstract : Purpose of review: By replacing sugar, nonnutritive sweeteners (NNSs) are thought to aid in weight management and decrease insulin resistance. We reviewed the latest randomized clinical trials (RCTs) investigating the effects NNSs on glycaemic control. Recent findings: Six RCTs addressed this topic between 2017 and 2018; the majority tested artificial NNS (sucralose or aspartame), with only one testing natural NNS (stevia and monk fruit extract). Most found no effect of NNS on blood glucose, insulin, gastric inhibitory polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) levels; however, two trials showed an effect of sucralose on the acute insulin response. Summary: We are still incapable of reaching a definite judgement on which types of NNS, if any, impact glycaemic control. There is a need for more research to overcome the limitations of recent RCTs, related to sample size, intervention duration, dose, form of NNSs used, and inclusion of males or female participants only. Future studies should also compare different NNS types with each other, and include the increasingly popular 'natural' NNS.